1981
DOI: 10.1111/j.1365-2125.1981.tb01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline pharmacokinetics in advanced age.

Abstract: 1 Theophylline kinetics following a single oral dose were characterized and compared in non‐institutionalized ambulatory elderly and young gender‐matched control subjects. Study design stressed stringent, yet realistic, control of several external factors known to influence theophylline metabolism. 2 Plasma levels of total drug were significantly higher in the elderly only at early sampling times (0.5 and 1 h) and at 36 h, while unbound theophylline levels were significantly higher (P less than 0.05) at all sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 14 publications
4
25
1
Order By: Relevance
“…This phenomenon was not seen by Schellens et al (1988) in young volunteers. Theophylline pharmacokinetics obtained in the present study are largely consistent with data published by others (Antal et al 1981;Boyce et al 1986;Chandler & Blouin 1988;Cohen et al 1985). Comparison of the pharmacokinetics in the healthy and frail elderly women shows that in the frail women the interindividual variability in the rate of metabolism is much larger than in the healthy elderly.…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon was not seen by Schellens et al (1988) in young volunteers. Theophylline pharmacokinetics obtained in the present study are largely consistent with data published by others (Antal et al 1981;Boyce et al 1986;Chandler & Blouin 1988;Cohen et al 1985). Comparison of the pharmacokinetics in the healthy and frail elderly women shows that in the frail women the interindividual variability in the rate of metabolism is much larger than in the healthy elderly.…”
Section: Discussionsupporting
confidence: 93%
“…Antal et al (1981) showed that total plasma theophylline concentrations were significantly higher in the elderly only at 0.5, I and 36 hours after administration. Unbound theophylline concentrations were significantly higher at all sampling times, resulting in a 45% greater area under the concentration-time curve for unbound drug (Antal et al 1981).…”
Section: Protein Bindingmentioning
confidence: 97%
“…Antal et al (1981) showed that total plasma theophylline concentrations were significantly higher in the elderly only at 0.5, I and 36 hours after administration. Unbound theophylline concentrations were significantly higher at all sampling times, resulting in a 45% greater area under the concentration-time curve for unbound drug (Antal et al 1981). Similarly, high concentrations of unbound sulphonylureas have been demonstrated in the elderly, which may be responsible for the increased incidence of hypoglycaemic events noted with these drugs in older patients (Miller et al 1977).…”
Section: Protein Bindingmentioning
confidence: 97%
“…It was postulated that the difference in theophylline metabolism shown in younger smokers was negated by the general decrease in drug metabolism with age. Antal et al (1981) studied the pharmacokinetics of theophylline in elderly adults (mean age 76 years) who were nonsmokers and concluded that there was 'less viable metabolism and renal excretion pathways for theophylline elimination in the elderly'. Cusack et al (1980) found that plasma theophylline half-life was shorter in the elderly who smoked compared with that in those who did not, but this could not be confirmed by Fox et al (1983).…”
Section: Introductionmentioning
confidence: 99%